Data-driven traffic sensor location and path flow estimation using Wasserstein metric - Gao, Jiaqi; Yang, Kai; Shen, Mengru; Yang, Lixing (Applied mathematical modelling, 2024)
This paper introduces link information value obtained by the traffic sensors and presents a traffic sensor location and flow estimation joint optimization model in an urban road network. In contrast to most previous studies, this paper adds new traffic sensors into the existing sensor network and proposes a data-driven path flow measurement method based on Wasserstein metric, which is utilized to measure the distance between the estimated traffic flow distribution and the actual distribution. Furthermore, this paper develops a customized greedy algorithm by combining a search strategy for the link information value to obtain the optimal sensor location scheme and perform traffic flow estimation under different budget conditions. Numerical experiments are conducted on Sioux-Falls test network and Eastern Massachusetts interstate highway subnetwork to verify the accuracy and effectiveness of the proposed model based on Wasserstein metric and the developed solution method. Computational results show that the sensor location scheme generated by the model based on Wasserstein metric can reduce the estimation error of the traffic flow compared with KL divergence model under the same deployment cost. Additionally, the customized greedy algorithm can achieve the better performance than the Brute force algorithm in terms of computing time and solution quality. •A traffic sensor location and path flow estimation joint optimization model is formulated.•A data-driven path flow measurement method based on Wasserstein metric is proposed.•A customized greedy algorithm by combining a search strategy is developed.•Numerical experiments are conducted based on the real-word transportation network.